Analisis Gaya Belajar Siswa dan Hubungannya dengan Hasil Belajar Menulis Aksara Jawa (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2023)
This study aims to describe the relationship between student learning styles and student learning outcomes in learning the Javanese language to write Javanese alphabet at SMP Darussalam Bergas. This research is a qualitative descriptive with 100 students of class VIII as the research subject. Data were collected through observation, interviews, questionnaires, and documentation. Analysis of the data using the analytical model of Miles and Huberman. The research steps consist of data collection, data reduction, data presentation, and drawing conclusions. The results of the study concluded that the learning styles of class VIII students when learning to write Javanese alphabet were 48% visual, 32% auditory, and 205 kinesthetic. Students who score above the cut score are dominated by auditory learning style, while students who score below the cut score are dominated by visual learning styles. The results of observations of students who have a visual learning style prefer to see the visual appearance of Javanese characters on the blackboard rather than just listening to the teacher's explanation. Students with an auditory learning style cannot concentrate if the class is in a crowded atmosphere. While students with a kinesthetic learning style prefer learning that involves students directly, they also cannot linger just sitting quietly and listening to the teacher's explanation.